The arcade of Frohse: a systematic review and meta-analysis - Benes, Michal; Kachlik, David; Kunc, Vladimír; Kunc, Vojtěch (Surgical and radiologic anatomy, 2021)
PURPOSE: The structure of the proximal margin of the superficial layer of the supinator muscle is of high interest to many researches. Its tendinous appearance, called the arcade of Frohse, may be clinically important because of its close relationship to the deep branch of the radial nerve passing beneath it and is considered to be the cause of several syndromes. Given the importance of this structure, we aimed to provide a comprehensive and evidence-based review with meta-analytic techniques. MATERIALS AND METHODS: The meta-analysis was performed in adherence to the PRISMA guidelines. Three medical databases were searched in order to identify all potentially eligible articles. Included studies were assessed for quality and the extracted morphological and morphometric data from the relevant articles was analyzed with the use of random effects meta-analysis. RESULTS: A total of 20 studies were included into this meta-analysis. The pooled prevalence of the arcade of Frohse was calculated to be 66% within the adult population and 0% in the fetuses. Other variations regarding the arcade of Frohse were identified as very rare. Analysis of the morphometric parameters revealed the average proportions to be 23.22 mm for the length, 11.05 mm for the width and the mean thickness is 0.67 mm. CONCLUSIONS: The arcade of Frohse is a commonly found structure in adults and thoughtful knowledge of its texture and morphology is especially useful in neurology, neurosurgery, orthopedics, trauma surgery and hand surgery, because it is considered to be the most common source of compression for the deep branch of the radial nerve.
Keywords: předloktí; ortopedické výkony; Radial Neuropathy; Forearm; Radial Nerve; šlachy; Muscle, Skeletal; Humans; neuropatie nervus radialis; Tendons; kosterní svaly; úžinové syndromy; nervus radialis; Orthopedic Procedures; lidé; Nerve Compression Syndromes